Menghadirkan Ruang Bercerita dalam Konteks Liturgi Generasi Z - Tesalonika, Gloria (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
Liturgy is often interpreted as a form of worship in the church. This interpretation is not entirely wrong. However, liturgy has a much broader understanding. Liturgy is an encounter between humans and God. There is two-way communication in this encounter: God takes the initiative to meet humans, and humans respond to God's touch that greets them. God's touch amid the struggling situations faced should be visible in the liturgy that is compiled. The liturgy needs to address the needs of everyone involved. This forms the basis for writing this article. The author focuses on the liturgy of young people belonging to Generation Z, born between 1995 and 2010, as they have unique struggles and challenges. The church needs to recognize the importance of the presence of young people and pay attention to their worship-related needs. This should be reflected in the liturgy to acknowledge their struggles and make storytelling space that is expressed, allowing them to experience an encounter with God. The method used is a qualitative method, with data collection techniques consisting of literature studies and interviews with young congregants attending worship services. This article offers a liturgical renewal by providing space for storytelling for Generation Z.